PERANAN AUDIT INTERNAL DALAM MENINGKATKAN PENGENDALIAN PIUTANG LAIN-LAIN PADA PT PUPUK KALIMANTAN TIMUR - Dessy Ambarsari; Bambang Hariadi (Jurnal Ilmiah Mahasiswa FEB, 2014)
Purpose of this research is to find out and assess internal audit role of other receivables on PT Pupuk Kalimantan Timur. Research method of this thesis is case study with descriptive method. Data is gotten by conducting interview, documentation, and observation. Credit sale is given to attract consumers so that the sale keeps increasing and the business can keeps running. However, credit sale causing vulnerable receivable such  as  uncollectible  receivable.  Therefore,  internal  audit  role  really  supports receivable control by conducting evaluation and giving recommendation to receivable internal control of the company. Evaluation of audit role based on other receivables is analyzed and evaluated by looking at internal  audit implementation and its impact toward internal control of other receivables whether it has run effectively. Result of the research indicates that internal audit role of PT Pupuk Kalimantan Timur is good enough so that it can increase other receivable control. Internal audit has given suggestion and recommendation supporting the improvement of receivable control of the company. However, result of the research also indicates that there is still weakness in other receivable of internal control namely document control whose validity period has been exhausted so that it needs special attention because it can be a barrier of uncollectible receivable.   Keywords: Internal Audit, Internal Control, Other Receivable